Execution of Scriplee Shares Secured in Fiduciary Security Following the Enactment of The Constitutional Court Decision Number 18/PUU-XVII/2019 - Sabrina Fauzanazila; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
Shares, as one of the securities traded on the Share exchange, can be issued in scripless form and the transaction settlement shall be carried out using book-entry settlement. The ownership of the scripless Share shall be evidenced in an electronic form, i.e. the ownership account at The Indonesia Central Securities Depository (KSEI) as the Depository and Settlement Institution in the  Indonesian Capital Market. As a movable object, shares can be used as debt collateral, one of which mechanism shall use fiduciary security. However, In a fiduciary security system, the control of such collateral remains with the fiduciary grantor. In terms of scripless Share collateral, KSEI will block the pledged shares in KSEI’s account, therefore, the shareholder shall have no longer control over such shares. The position of the fiduciary grantee is prioritized over other creditors due to the executorial power deemed having the same legal force as a legally bound court decision. However, following the enactment of the Constitutional Court Decision Number 18/PUU-XVII/2019 regarding the judicial review of Law No. 42 of 1999 concerning Fiduciary Guarantees, there is a provision that any fiduciary execution cannot be carried out without an agreement among the parties regarding the default by the borrower. The method used in this research is descriptive-analytical using a normative juridical approach bu utilizing secondary data i.e. regulations in capital market, fiduciary security and Constitution Court Judicial Review Decree.